KUALITAS REMAJA DI KABUPATEN BANYUMAS - Suksmadi, Ignatius; Sumarwan, Ujang; Khomsan, Ali; Hartoyo, Hartoyo (Jurnal Ilmu Keluarga dan Konsumen, 2009)
This research was aimed at analyzing indicator of early adolescent quality and factors affecting the early adolescent quality (EAQ). The study tried to create EAQ index and to analyze its effect to academic achievement. EAQ was measured by body mass index (physical dimension), intelligent quotient and emotional intelligent (nonphysical dimension). The index could show the different quality among public and private school. A crosssectional study was applied on this study. The location were purposively selected at five subdistricts, i.e., Purwokerto, Baturaden, Ajibarang, Rawalo, and Sumpiuh. Total samples of the study were 300 students of secondary school and their families. The sample were divided into public school samples (150 students) and private school samples (150 students). The study created the EAQ categorized in four category, i.e., high (7,7%), medium (71,3%), low (20,7%), and very low (0,3%). The study described that both student (public and private school) have significant differences on EAQ, academic achievement, school environment. Yet, the study found no significant differences of home environment between public and private school samples. The public school amples had the better EAQ, academic achievement, and school environment  than the private school samples. The regression analysis showed that home and school environment, education investment factors affected EAQ. Academic achievement was influenced by EAQ, parent’s control on student time, school condition, student activity involvement, family monetary investment, year of schooling of mother, and student expectation.